Supporting the integration of refugee and asylum-seeking health professionals into the South African Health System - Rampersad, Prashana (Graduate School of Business (GSB), 2026)
This dissertation explores the integration challenges faced by refugee and asylum-seeking health professionals in gaining professional recognition and accessing employment in health professions in South Africa. Despite South Africa's progressive legal framework, practical pathways for qualification recognition and professional inclusion remain fragmented and exclusionary. While much of the literature focuses on low-skilled labour market integration and survival strategies, the experiences of highly skilled refugee and asylum seeker professionals are often overlooked, leading to their marginalisation and the underutilisation of their health expertise. Using a qualitative approach, the research draws on semi-structured interviews with 16 refugee and asylum-seeking health professionals in Cape Town and four institutional representatives from the South African Qualifications Authority, the Foreign Workforce Management and the Western Cape Department of Health. Vignettes are used to humanise participants' experiences and foregrounding the personal stories behind the systemic barriers to professional integration. This study is grounded in Bourdieu's theory of capital, examining how refugee and asylum seeker economic, social, cultural and symbolic capital is systematically devalued. It also incorporates critical perspectives on integration, drawing from Ager and Strang's (2008) multidimensional framework and newer research that highlight how integration can involve unequal power relationships and unfair expectations (Spencer & Charsley, 2021). In doing so, the research highlights how historical and institutional legacies; shaped by apartheid, xenophobia, and rigid bureaucracy, reproduce structural and symbolic violence that undermines refugee professionals' access to dignified work. By identifying and interrogating the structural barriers to recognition, this dissertation argues that structural barriers prevent refugee and asylum seeker health professionals from being recognised. The creation of practical and inclusive pathways to professional integration is essential for the restoration of their dignity and ability to contribute to South Africa's healthcare system. The findings offer a critical and contextually grounded contribution to debates on refugee integration, institutional power, and inclusive health workforce development.